2019
DOI: 10.17073/0368-0797-2019-7-539-547
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal state of the end area of multiple continuous-cast billet on cracking of the ends of hot-rolled breakdown at rolling

Abstract: The authors have made an analysis of problems arising in the rolling of continuous-cast billets in the modern mini-metallurgical and rerolling plants. It is shown that the use of trio stands in rolling mills of these plants makes it necessary to obtain billets of multiple lengths from bars (most often of 12-meter length) produced in the rolling shop. The subsequent rolling of such multiple billets has revealed increased cracking of the front edge and, as a result, increased metal consumption. Analysis of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Tselikov et al [23] concluded that the accumulated tensile stress in the central region of the workpiece during the rolling was key. However, by analysing the stress state in rotary compression, Smirnov and Lunvev [24,25] suggested that the secondary tensile stress generated by the normal compression was the main cause. From experimental observation, Guzavichus et al [26] found that the strong velocity gradient between workpiece flanges and steps led to strong torsional forces which increased during rotation, generating strong shear stress and causing the final fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Tselikov et al [23] concluded that the accumulated tensile stress in the central region of the workpiece during the rolling was key. However, by analysing the stress state in rotary compression, Smirnov and Lunvev [24,25] suggested that the secondary tensile stress generated by the normal compression was the main cause. From experimental observation, Guzavichus et al [26] found that the strong velocity gradient between workpiece flanges and steps led to strong torsional forces which increased during rotation, generating strong shear stress and causing the final fracture.…”
Section: Introductionmentioning
confidence: 99%